The Influence of Service Quality on Customer Loyalty Mediated by Customer Satisfaction at Janji Jiwa Coffee Shop Malangg - Adinda Rizki Yuanitasari; Ratih Jualiati; Ardik Praharjo (Jamanika (Jurnal Manajemen Bisnis dan Kewirausahaan), 2022)
This study aims to examine the effect of service quality on customer loyalty with customer satisfaction as a mediating variable. The type of research used is explanatory research. The population used is customers who have visited the Janji Jiwa Malang coffee shop. The sampling method used is non-probability sampling with an accidental sampling technique. The sample used was 100 respondents. The data collection method used a questionnaire, then the data that had been collected were analyzed using path analysis. The results of this study were service quality has a positive and significant effect on customer loyalty. Â Customer satisfaction has a positive and significant effect on customer loyalty. Service quality has a positive and significant effect on customer satisfaction and customer satisfaction can mediate the effect of quality. service to customer loyalty.